An Empirical Assessment of Factors Influencing Injury Severities of Motor Vehicle Crashes on National Highways of Pakistan - Hanif Ullah; Asim Farooq; Akhtar Ali Shah (Journal of Advanced Transportation)
Road transport is the dominant mode of transport in Pakistan carrying 91% of the country’s passenger traffic and 96% of freight traffic. National highways, being 3.7% of the entire road network, carry 80% of commercial traffic. Due to the high number of road traffic crashes and resulting fatalities, a random parameters logit model was estimated to determine the risk factors that influence the severity of injuries caused by motor vehicle crashes on national highways. The effects of driver characteristics, crash characteristics, highway characteristics, temporal characteristics, and environmental characteristics were considered for the analysis. From the results, it was revealed that many factors such as overspeeding, driver dozing, driver carelessness, driver age <25 years, truck, rickshaw, single vehicle, horizontal curve, potholes, night without road lights, AM peak, Tuesday, weekdays, May, July, November, cloudy weather, clear weather, normal visibility, and wet road surface affect injury severity of the crash victims. The results are expected to be useful for transport planners, traffic managers, road engineers, and other stakeholders both from public and private sectors in prioritizing road sections for improvements and implementing suitable road safety interventions. This will ultimately result in the decreased social and economic burden of road traffic injuries (RTIs).